Experimental investigation of nonlinear springing and fatigue assessment of a 308, 000 DWT oil tanker and a 205, 000 DWT bulk carrier in a basin. (1st December 2020) - Yang, Peng; Zhang, Wei; Ding, Jun; Gu, Xuekang; Chen, Haosen
Abstract: In the IACS harmonized common structural rules, it is hoped that the fatigue damage to ship structures caused by springing can be rationally analysed. In the case of limited resources in a basin, it is impossible to carry out model tests of wave-induced vibrations for many short-term sea states. Based on wave load transfer function under regular waves, a simplified method is established to evaluate the nonlinear springing and fatigue damage to ship structures under many different short-term and long-term sea states and is proposed by using wave loads of wave-frequency and high-frequency components. The wave loading model tests of a 308, 000 DWT VLCC (very large crude container) and a 205, 000 DWT VLBC (very large bulk carrier) are carried out; moreover, the springing influence on structural fatigue is assessed in short-term sea states by using stress data measured from model tests. Furthermore, the springing influence on structural fatigue is studied in long-term sea states for some typical sea routes. It is concluded that the impact of springing is obvious on a VLCC and VLBC under ballast conditions and differs for various routes. The simplified method can assess the fatigue damage due to springing properly. Highlights: A simplified method is proposed to calculate nonlinear wave-induced vibrations based on load transfer functions in regular waves. The ten-segmented model tests of a 308, 000 DWT very large crude carrier and a 205, 000 DWT bulk carrier are carried out in tower tank. The ratios of fatigue damage between considering springing and without springing are respectively 1.37 ~ 2.45 and 1.21 ~ 1.52 for the VLCC and the VLBC.